Peningkatan Kapasitas Bidan dalam Pelaksanaan Pemantauan dan Edukasi tentang Berat Badan Berdasarkan Status IMT Prahamil di Kabupaten Mempawah Provinsi Kalimantan Barat - Sulistiawati, Rini; Damayanti, Dini Fitri; Fajrin, Dessy Hidayati (Politeknik Kesehatan Kemenkes malang, 2023)
Monitoring pregnant women's weight gain based on pre-pregnancy Body Mass Index (BMI) can assist health workers in making appropriate clinical decisions and educational interventions about diet and physical activity of pregnant women. The results showed that specific weight gain education for pregnant women based on pre-pregnancy BMI status was effective on the suitability of increasing pregnant women's weight, so interventions to increase midwifery knowledge were needed in an effort to increase the ideal weight of pregnant women. The Pontianak Ministry of Health Polytechnic conducts community service every year in realizing the tridarma of higher education, one of which is through